The Influence of Impulsivity, Promotional Exposure, and Product Variety on Impulsive Clothing Purchase Decisions Through Positive Emotions (A Case Study of Female Students at STIESIA) - Khatrin Kulman Makuku; Suwitho Suwitho (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to examine the direct and indirect effects of impulsivity, promotional exposure, and product variety on impulsive clothing purchase decisions through positive emotions. The population consisted of female students at the Indonesia School of Economics (STIESIA) Surabaya. The sampling technique employed was purposive sampling, resulting in a total of 97 respondents. Data were collected using a questionnaire and analyzed using the Partial Least Squares (PLS) method. The results indicate that impulsivity, promotional exposure, product variety, and positive emotions each have a significant effect on impulsive clothing purchase decisions. Product variety has a significant effect on positive emotions, whereas impulsivity and promotional exposure do not significantly affect positive emotions. Furthermore, the findings reveal that positive emotions do not mediate the relationship between impulsivity and impulsive clothing purchase decisions, nor do they mediate the relationship between promotional exposure and impulsive clothing purchase decisions. However, positive emotions do mediate the relationship between product variety and impulsive clothing purchase decisions.